Density Mangrove Relationship with Gastropod Abundance in the Sungai Alam Village, Bengkalis Sub-district, Bengkalis Regency, Riau Province - Hendri, Faisal; Fajri, Nur El; ', Adriman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted in January - February 2014 in the mangrove forests SungaiAlam Village Bengkalis Sub-district Bengkalis Regency Riau Province. This research aims todetermine the type of mangrove, the type of gastropods, as well as the mangrove density ofrelationship with gastropod abundance in the sungai alam village. The results of researchfound 7 species of mangrove: Avicennia alba, Sonneratia alba, Rhizophora apiculata,Rhizophora mucronata, Rhizophora stylosa, Xylocarpus sp and Lumnitzera sp. Mangrovedensity first station with a total of tree was 2.834 tree/ha, in second station with a total of treewas 3.967 tree/ha and in thrid at three station with a total of tree 4.234 tree/ha. gastropodsfound are 11 species: Nerita funiculata, Cerithidea quadrata, Chicoreus capucinus,Cassidula lutescens, Telescopium telescopium, Ellobium aurisjudae, Littoraria scabra,Littoraria melanostoma, Thais carinifera, Dostia violacea dan Terebralia sulcata, abundanceof gastropods in first station was 85.185 ind/ha, in second stations was 100.000 ind/ha, and inthird station was 203.333 ind/ha. The regression line test between mangrove density withabundance of gastropods showed the equation Y = 10327 + 63,28 x with the determinationcoefisien (R2) is 0,534. Increasing the density of mangrove gastropod abundance is increasingas well.Key Words : Mangrove density, Gastropods abudance, Sungai Alam Village, BengkalisRegency